The Diachronic Use of the Word ‘Halal’ in Republika.co.id: A Corpus-Based Analysis (2010–2022) - Suhandano Suhandano; Aris Munandar; Taat Budiono (Master Program in Linguistics, Diponegoro University, 2026)
The expanding use of the word halal in Indonesian has become a prominent phenomenon. Despite this development, empirical diachronic studies that systematically examine the evolution of the word halal in Indonesian public discourse remain limited. This study addresses two research questions: (1) How has the use of the word halal evolved in Republika.co.id from 2010 to 2022? Moreover, (2) What topics were discussed in relation to the use of the word halal during this period? Adopting a corpus-based approach, this study utilises the corpus analysis tool Sketch Engine to examine a corpus of 1,132 news articles on halal published by Republika.co.id between 2010 and 2022. The findings indicate that the use of the word halal increased markedly, particularly during the final four years (2019–2022). This surge coincided with several key policy initiatives introduced by the Indonesian government, including the implementation of mandatory halal certification, the establishment of halal industrial zones, and the promotion of a broader halal ecosystem. Collocation analysis further reveals a notable expansion in the discourse’s thematic scope. While early coverage primarily focused on halal products, discussions gradually shifted toward broader themes related to the halal industry and halal economy. Overall, this study provides an empirical account of the diachronic transformation in the use of the word halal in mass media and demonstrates a correlation between government policy agendas and the dynamics of public discourse.